Cardiac hemodynamics in alcoholic patients with chronic liver disease and a presystolic gallop - Gould, Lawrence; Shariff, Mahmood; Zahir, Mohammad; Lieto, Mary Di (The Journal of Clinical Investigation, 1969)
10 male subjects with chronic liver disease and with normal cardiovascular findings, except for the presence of a presystolic gallop, underwent right and left heart catheterization. In general, all of the patients had a high resting cardiac output, narrow arteriovenous oxygen difference, a low peripheral vascular resistance, and normal left ventricular end-diastolic pressures and volumes. The plasma volume was increased in the seven patients in which it was determined. On exercise, all of the patients demonstrated a significant increase in the left ventricular end-diastolic pressure and mean pulmonary artery pressure, while the stroke index remained the same or fell in seven of the subjects. It appears logical to assume that the excessive intake of alcohol is associated with an impairment in the metabolic and contractile properties of the left ventricle and the resultant hemodynamic effects may not be readily discerned in the resting state. However, upon exercise these patients, with a congested circulation, can show abnormal cardiac dynamics. Images